Apolipoprotein E-Containing Lipoproteins Protect Neurons from Apoptosis via a Signaling Pathway Involving Low-Density Lipoprotein Receptor-Related Protein-1 - Hayashi, Hideki (J Neurosci, 2007)
Apolipoprotein E (apoE)-containing lipoproteins (LPs) are secreted by glia and play important roles in lipid homeostasis in the CNS. Glia-derived LPs also promote synaptogenesis and stimulate axon growth of CNS neurons. Here, we provide evidence that glia-derived LPs protect CNS neurons from apoptosis by a receptor-mediated signaling pathway. The protective effect was greater for apolipoprotein E3 than for apolipoprotein E4, the expression of which is a risk factor for Alzheimer's disease. The anti-apoptotic effect of LPs required the association of apolipoprotein E with lipids but did not require cholesterol. Apoptosis was not prevented by lipids alone or by apoA1- or apoJ-containing lipoproteins. The prevention of neuronal apoptosis was initiated after the binding of LPs to the low-density lipoprotein receptor-related protein (LRP), a multifunctional receptor of the low-density lipoprotein receptor family. We showed that inhibition of LRP activation, by treatment of neurons with receptor-associated protein or anti-LRP antibodies, or by LRP gene-silencing experiments, reduced the protective effect of LPs. Furthermore, another LRP ligand, α(2)-macroglobulin, also protected the neurons from apoptosis. After binding to LRP, LPs initiate a signaling pathway that involves activation of protein kinase Cδ and inactivation of glycogen synthase kinase-3β. These findings indicate the potential for using glial lipoproteins or an activator of the LRP signaling pathway for treatment for neurodegenerative disorders such as Alzheimer's disease.